COVID-19 infection after SARS-CoV-2 mRNA vaccination in Multiple Sclerosis, AQP4-antibody NMOSD and MOGAD patients during the Omicron subvariant BA.1/2 wave in Singapore - Yeo, Tianrong (2023)
Background: The SARS-CoV-2 Omicron variant appears to cause milder infections, however, its capacity for immune evasion and high transmissibility despite vaccination remains a concern, particularly in immunosuppressed patients. Herein, we investigate the incidence and risk factors for COVID-19 infection in vaccinated adult patients with Multiple Sclerosis (MS), Aquaporin-4-antibody Neuromyelitis Optica Spectrum Disorder (AQP4-Ab NMOSD), and Myelin Oligodendrocyte Glycoprotein-antibody associated disease (MOGAD) during the Omicron subvariant BA.1/2 wave in Singapore. Methods: This was a prospective observational study conducted at the National Neuroscience Institute, Singapore. Only patients who had at least two doses of mRNA vaccines were included. Data on demographics, disease characteristics, COVID19 infections and vaccinations, and immunotherapies were collected. SARS-CoV-2 neutralising antibodies were measured at various time points after vaccination. Results: Two hundred and one patients were included; 47 had COVID-19 infection during the study period. Multivariable logistic regression revealed that receipt of a third SARS-CoV-2 mRNA vaccination (V3) was protective against COVID-19 infection. No particular immunotherapy group increased the risk of infection, however, Cox proportional-hazards regression showed that patients on anti-CD20s and sphingosine-1-phosphate modulators (S1PRMs) had a shorter time to infection after V3, compared to those on other immunotherapies or not on immunotherapy. Conclusions: The Omicron subvariant BA.1/2 is highly infectious in patients with central nervous system inflammatory diseases; three doses of mRNA vaccination improved protection. However, treatment with anti-CD20s and S1PRMs predisposed patients to earlier infection. Future studies are required to determine the protective efficacy of newer bivalent vaccines that target the Omicron (sub)variant, especially in immunocompromised patients.